Os modos de contar: estudos da telenovela brasileira - Garrán, Pablo Turbuk (2015)
This research aimed to analyze how the soap operas, as mass communication tools, operationalize and interfere in the constitution of society cultural repertoire, from the soap opera "Amor à Vida", displayed on Rede Globo Television in the period from 05/20/2013 to 01/31/2014. At the first stage we trace a brief history of soap opera as a language, its origins in literature and oral narrative and its interface with the cinema; in a second moment, we examine the role of the soap opera as mass diffuser vehicle, its contradictions and the soap opera as a product and in the third moment we discussed the use of image features such as communication strategies, approaching: photography, lighting, sets, costumes, makeup, camera angles, cuts, scenes duration, among other elements. We work with communication theories developed by Gabriel Tarde, as well as with other authors that contribute to the formulation of this analysis, as Propp. For the analysis of the soap opera, the work with documentary research was chosen because of the basis of this research occur from primary written sources, in other words, without analytic treatment, such as newspapers, magazines and websites